2000
DOI: 10.1007/s11627-000-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

Thidiazuron promotes in vitro regeneration of wheat and barley

Abstract: SummaryThidiazuron (TDZ) is a substituted phenylurea which has been shown to be an efficacious regulator of in vitro morphogenesis of many dicot plant species. However, information regarding the effect of TDZ on in vitro regeneration of monocot species is limited. We investigated the effects of TDZ on in vitro regeneration of barley (Hordeum vulgare L.) and wheat (Triticum aestivum L.) and found that it promoted shoot regeneration from callus in these two important cereal species. Plant regeneration from callu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 20 publications
3
28
2
1
Order By: Relevance
“…As citocininas promovem a proliferação celular dos meristemas laterais, quebram a dormência de gemas em videira e macieira e facilitam a proliferação de múltiplos brotos em algumas culturas (GAIRI e RASHID, 2004;SRIVATANAKUL et al, 2000), incluindo o arroz (YOOKONGKAEW et al, 2007) e outras espécies como feijão (MOHAMED et al, 2006) e trigo (SHAN et al, 2000). Liu et al, (2011) indicam que o desenvolvimento de gemas que originam perfilhos nas plantas de arroz é estimulado pela citocinina, de modo que o aumento no nível desses hormônios favorece o perfilhamento.…”
Section: Resultsunclassified
“…As citocininas promovem a proliferação celular dos meristemas laterais, quebram a dormência de gemas em videira e macieira e facilitam a proliferação de múltiplos brotos em algumas culturas (GAIRI e RASHID, 2004;SRIVATANAKUL et al, 2000), incluindo o arroz (YOOKONGKAEW et al, 2007) e outras espécies como feijão (MOHAMED et al, 2006) e trigo (SHAN et al, 2000). Liu et al, (2011) indicam que o desenvolvimento de gemas que originam perfilhos nas plantas de arroz é estimulado pela citocinina, de modo que o aumento no nível desses hormônios favorece o perfilhamento.…”
Section: Resultsunclassified
“…TDZ (Thidiazuron) is a substituted phenyl urea [1-phenyl-3-(1,2,3-thidiazol-5-yl)urea] that has immense potential as a cytokinin in shoot organogenesis in a large number of plant systems including legumes (Murthy et al, 1998;Shan et al, 2000;Ganeshan et al, 2003;Onamu et al, 2003;Mroginski et al, 2004;Sharma et al, 2005;Chen and Chang, 2006;Radhika et al, 2006). Since, the observation made by Malik and Saxena (1992) TDZ has been noted to be the most promising cytokinin for shoot induction in chickpea by number of research teams (Barna and Wakhlu, 1993;Huetteman and Preece, 1993;Murthy et al, 1996;Rizvi and Singh, 2000;Jayanand et al, 2003;Senthil et al, 2004;TewariSingh et al, 2004;Kiran et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…This showed that the low concentration of IBA in combination with BAP or TDZ was needed for shoot regeneration of sorghum. Shan et al (2000) and Aparna and Rashid (2004) demonstrate that TDZ is an important hormone for the regeneration of cereal and grass species and the production of multiple shoots. Sorghum regeneration is affected by genotype (Baskaran and Jayabalan 2005), which may be due to changes in gene expression, which in turn depends on the spatial and temporal repartition of physiological stages (Vasil and Vasil 1986).…”
Section: Discussionmentioning
confidence: 99%